2018
DOI: 10.1080/17453674.2018.1431854
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of cancer after primary total hip replacement: The influence of bearings, cementation and the material of the stem

Abstract: Background and purposeDespite the increasing number of total hip replacements (THRs), their systemic influence is still not known. We have studied the influence of specific features of THRs—the bearing surface, the use of bone cement and the material of the stem—on the cancer incidence.Patients and methodsIn a retrospective cohort study we identified 8,343 patients with THRs performed at Valdoltra Hospital from September 1, 1997 to December 31, 2009. Patient data were linked to national cancer and population r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“… 2010 , Levasic et al. 2018 ). No increase in the risk of melanoma was found for patients treated with a MoM resurfacing device (Brewster et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2010 , Levasic et al. 2018 ). No increase in the risk of melanoma was found for patients treated with a MoM resurfacing device (Brewster et al.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Slovenia including only THAs found a slightly higher risk of overall cancer in patients treated with MoM bearing when compared with the general population or the non-MoM patients (Levasic et al. 2018 ). In that study the specific cancer types that had higher prevalence in the MoM cohort compared with the general population were skin cancers excluding melanoma and prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Only one Finnish study compared MoM and MoP hip prostheses [ 22 ] finding no difference in all cause cancer incidence between the procedures. One study in Slovenia found that the risk for all cancers combined as well as for prostate and skin cancer was higher with MoM compared to non-MoM procedures (RR = 1.56; 2.02 and 1.92, respectively) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…induce malignant degeneration, the relationship has not been well demonstrated. Many studies have examined the differential risk of cancer between different bearing surfaces, results have varied [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous retrospective cohort studies have been conducted to investigate the association between orthopaedic metal implants and cancer development. Some studies have reported an increased risk of certain types of cancer, including lymphoma, prostate cancer, and melanoma [19][20][21]. In particular, higher prostate and skin cancer risk was identified in a MoM cohort compared to the non-MoM cohort [19].…”
Section: Introductionmentioning
confidence: 97%